The maintenance of an oral epithelial barrier - Wang, Sha-Sha; Tang, Ya-Ling; Pang, Xin; Zheng, Min; Tang, Ya-Jie; Liang, Xin-Hua (Life sciences (1973), 2019)
Oral epithelial barrier consists of closely controlled structure of the stratified squamous epithelium, which is the gateway to human bodies and encounters a huge burden of microbial, airborne and dietary antigens, as well as masticatory damage. Once this barrier is destroyed, it will trigger bone loss, tissue damage and microbial dysbiosis and lead to diseases, such as periodontitis, oral mucosal diseases and oral cancer. Recently, increasing evidences showed that different factors including microorganism, saliva, proteins and immune components have been considered to play a critical role in the disruption of oral epithelial barrier. Herein, we discussed mechanisms governing the maintenance of oral epithelial barrier. Besides, the role of oral epithelial barrier failure in oral carcinogenesis will also be talked about. Oral epithelial barrier is made up of keratinocytes and is maintained by intercellular junctions and cornified envelope. Keratins are crucial proteins that constitute both cytoskeleton and tight junctions, among which the defects of keratin 5 (k5) and k14 result in epidermolysis bullosa simplex. Keratins could also be dissolved by proteases produced by P. gingivalis, leading to gingival barrier failure, attachment loss and periodontal destruction in periodontitis. The cornified envelop of stratum corneum is composed of extracellular proteins like keratins that provide for mechanical resilience, and special lipids such as ceramides which fill extracellular spaces and regulate the permeability of the oral epithelial barrier. [Display omitted]